PERHITUNGAN WAKTU BAKU DAN PENENTUAN PRODUKTIVITAS PADA PENGERJAAN PEMBERSIHAN KACA GEDUNG X - Ujang Juwardi; Septian Rahmat Adnan; Taufiqur Rachman; M. Derajat Amperajaya; Nofi Erni; Roesfiansjah Rasjidin; Musfirah Cahya Fajrah (Universitas Negeri Jakarta, 2023)
XYZ is a company that provides building maintenance services; one of its services is glass cleaning services. In every work on building maintenance services projects in the form of cleaning the glass of PT. XYZ has not calculated the standard time of work, which affects 45% of the total work exceeding the deadline for the job given and the difficulty of estimating the productivity of the workers. In this study, the standard time and productivity were determined on the glass cleaning work of building X using the stopwatch time study method. The results of the calculations carried out using the stopwatch time study method obtained the optimal normal time at each stage of the work, namely in the preparation of work equipment for 58.55 minutes, on the removal of the gallows 112.82 minutes, on the installation of ropes of 20.41 minutes, on machine checking is 22.29 minutes, glass cleaning is 54.17 minutes, rope disassembly process is 57 minutes, and gondola storage is 55.33 minutes so that the optimal standard time is 380.56 minutes. Calculation results showed that performance rating measurement, excellent skill is B1 +0.11, a good effort is C1 +0.05, good condition is C +0.02, consistency is C +0.01 with a rating factor obtained in normal time is 65.569 minutes, and from the results of the calculation of worker productivity in the work of cleaning the glass of building X was obtained 0.12 units/hour.